The Influence of the Import Ban Policy on Secondhand Goods on Traders’ Income Perception from the Perspective of Islamic Economics Case Study at Pasar Jongkok Tembilahan City Indragiri Hilir Regency - Yuliarni Nur Habiba; Qusthoniah; Said Abdul Aziz (Journal Of Social Siences And Islamic Studies (JOSIS), 2026)
This study investigates the impact of the import ban on secondhand goods on traders’ perceptions of income and evaluates the policy within the framework of Islamic economics. The issue is relevant as such policies often create disparities, particularly for small-scale traders who depend on imported secondhand goods. Employing a quantitative approach with purposive sampling, data were collected from 53 active traders through questionnaires, interviews, and documentation. The analysis was conducted using SPSS 25 with a Simple Linear Regression model. The results reveal a regression equation of Y = 27.624 – 0.275 (Import Ban Policy) + e. The t-test shows that the policy negatively and significantly affects traders’ income (t = –9.962, p < 0.05), while the coefficient of determination (R² = 0.661) indicates that 66.1% of the variance in income perception is explained by the policy. From an Islamic economics perspective, the policy must be assessed through the principles of maqashid sharia, including justice, public interest, social responsibility, and protection of wealth. While the ban may serve public welfare, its execution should ensure fairness to prevent harm to small traders. The study concludes that more balanced and responsive policy measures are required to safeguard economic justice.